Service Quality and Customer Satisfaction: The Key to Repurchase Intention for Travel Packages - Fadillah, Fadillah; Lubis, Rahmi; Patisina, Patisina (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Service quality is one of the key factors in the tourism industry as it shapes customer satisfaction and fosters consumer loyalty. Positive experiences perceived by tourists through direct interactions with service providers strengthen their intention to make repeat purchases (repurchase intention). This study analyzes the effect of service quality on customer satisfaction and repurchase intention in tour packages, with customer satisfaction as a mediating variable. The research employed a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS). The sample was obtained through purposive sampling from consumers who had used tour package services. The results show that service quality has a positive and significant effect on customer satisfaction (coefficient = 0.442; T-Statistic = 7.947; P-Value = 0.000) and repurchase intention (coefficient = 0.592; T-Statistic = 9.380; P-Value = 0.000). In addition, customer satisfaction also positively influences repurchase intention (coefficient = 0.393; T-Statistic = 6.968; P-Value = 0.000). The f-square analysis indicates that the direct effect of service quality on repurchase intention falls into the large category with 51.76%, while the mediating contribution of customer satisfaction is 22.71% with a medium effect size. These findings highlight that service quality influences repurchase intention not only directly but also indirectly through customer satisfaction. The practical implication of this study emphasizes the importance for tourism service providers to maintain consistent, reliable, and customer-oriented service quality in order to create sustainable satisfaction and enhance repurchase intention.Kualitas pelayanan merupakan salah satu faktor kunci dalam industri pariwisata karena mampu membentuk kepuasan dan mendorong loyalitas konsumen. Pengalaman positif yang dirasakan wisatawan dari interaksi langsung dengan penyedia layanan akan memperkuat niat untuk melakukan pembelian ulang (repurchase intention). Penelitian ini menganalisis pengaruh kualitas pelayanan terhadap kepuasan konsumen dan repurchase intention pada paket wisata, dengan kepuasan konsumen sebagai variabel mediasi. Metode penelitian menggunakan pendekatan kuantitatif dengan analisis Structural Equation Modeling-Partial Least Square (SEM-PLS). Sampel diperoleh melalui teknik purposive sampling dari konsumen pengguna jasa paket wisata. Hasil penelitian menunjukkan bahwa kualitas pelayanan berpengaruh positif dan signifikan terhadap kepuasan konsumen (koefisien = 0,442; T-Statistik = 7,947; P-Value = 0,000) dan repurchase intention (koefisien = 0,592; T-Statistik = 9,380; P-Value = 0,000). Selain itu, kepuasan konsumen juga berpengaruh positif terhadap repurchase intention (koefisien = 0,393; T-Statistik = 6,968; P-Value = 0,000). Analisis f-square menunjukkan pengaruh langsung kualitas pelayanan terhadap repurchase intention termasuk kategori besar sebesar 51,76%, sedangkan kontribusi kepuasan konsumen sebagai mediator sebesar 22,71% dengan kategori efek sedang. Temuan ini menegaskan bahwa kualitas pelayanan tidak hanya memengaruhi niat beli ulang secara langsung, tetapi juga melalui kepuasan konsumen. Implikasi praktis dari penelitian ini adalah perlunya penyedia jasa wisata menjaga kualitas pelayanan yang konsisten, ramah, dan sesuai kebutuhan pelanggan agar tercipta kepuasan yang berkelanjutan serta meningkatkan repurchase intention.